Tort Law and the Ethical Responsibilities of Liability Insurers: Comments from a Reinsurer’s Perspective - Lahnstein, Christian (2011)
Tort law and liability insurance have a complex interaction in which each shapes the evolution and effects of the other. This interaction and its many forms and facets in different international contexts must be comprehended to understand fully the ethical responsibilities of liability insurers. This essay builds on previous scholarship on the tort law–liability insurance interaction through a series of observations from the perspective of a global reinsurer. It seeks in part to extend previous analyses of this interaction by also considering issues in the developing world. It seeks to make some normative questions and stances explicit concerning this interaction, as well as to identify some empirical questions that still need to be answered. The responsibility of liability insurers includes ethically shaping the responsibility of others in interaction with tort law in countless diverse situations.
Keywords: Liability insurance; First-party insurance; tort law